2011
DOI: 10.1111/j.1559-1816.2011.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Control and Junk‐Food Consumption: A Mediating and Moderating Effect Analysis1

Abstract: This cross‐sectional study examined the mediating effect of the theory of planned behavior (TPB) and the moderating role of perceived parental control within the context of adolescents' junk‐food consumption. Adolescents (N = 739) were selected using a cluster‐stratified randomized sampling method. Social cognitions, perceived parental control, and junk‐food consumption were assessed through self‐administered questionnaires. Results revealed both direct and indirect effect of perceived parental control within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…The included interaction term between target's and friend's self-monitoring scores proved to be nonsignificant and did not change the global pattern of results observed. Furthermore, the choice of assessing self-reported past or usual consumption as a dependent variable is common in research aimed at explaining adolescents' eating behavior (e.g., Karimi-Shahanjarini et al, 2012;Lally, Bartle & Wardle, 2011;Powell & Han, 2011;Woodruff & Hanning, 2009), and a systematic review (Brener, Billy, & Grady, 2003) showed that the cognitive factors affecting adolescents' self-reported food consumption do not threaten the validity of these self-reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The included interaction term between target's and friend's self-monitoring scores proved to be nonsignificant and did not change the global pattern of results observed. Furthermore, the choice of assessing self-reported past or usual consumption as a dependent variable is common in research aimed at explaining adolescents' eating behavior (e.g., Karimi-Shahanjarini et al, 2012;Lally, Bartle & Wardle, 2011;Powell & Han, 2011;Woodruff & Hanning, 2009), and a systematic review (Brener, Billy, & Grady, 2003) showed that the cognitive factors affecting adolescents' self-reported food consumption do not threaten the validity of these self-reports.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, both correlational (e.g., Birch & Fisher, 2000) and longitudinal (e.g., Birch, Fisher, & Davison, 2003) studies investigating the consequences of these practices in terms of children's eating behavior, food preferences and body weight, indicated that external control has counterproductive effects. However, other studies suggested that the presence of rules disciplining the access to food in families is associated with healthier diets among children (e.g., Brown, Ogden, V€ ogele, & Gibson, 2008) and adolescents (e.g., Karimi-Shahanjarini, Rashidian, Majdzadeh, Omidvar, Tabatabai, & Shojaeezadeh, 2012). Directing children's food choices is thus not always detrimental: the effectiveness of nutrition related parenting practices seems to depend on the way they are put to use.…”
Section: Authoritative Parenting Style and Parental Modelingmentioning
confidence: 99%
“…A 23-item qualitative Food Frequency Questionnaire (FFQ) was used to measure the frequency of unhealthy snacks consumption, as the dependent variable with a count scale (0 = never consumed to 1, 2, 3, …). This questionnaire was firstly obtained from Karimi-Shahanjarini et al study 29 and then was modified following short semi-structured interviews with fifty students (from middle schools with similar characteristics of the study sample) and common snacks suppliers at 5 school canteens in Kerman city. Face and content validity of the questionnaire were assessed by sending it to 5 nutrition experts.…”
Section: Methodsmentioning
confidence: 99%
“…The theory of planned behavior has demonstrated efficacy as a conceptual framework for examining the antecedents of behaviors and effecting behavior change. Themodel has been used to examine a range of health behaviors (Duncan, Forbes-McKay, & Henderson, 2012;Karimi-Shahanjarini et al, 2012;Louis et al, 2007), socially-minded behaviors such as energy conservation (Nolan et al, 2008) and charitable intentions to donate (Knowles et al, 2012), and hundreds of other behaviors (Armitage & Conner, 2001). In recent years, researchers have examined the utility ofthe TPB in relation to online behaviors, such as online musicpiracy (d'Astous et al, 2005), online stock trading (Lee, 2009), and online privacy protection (Yao & Linz, 2008;Yousafzai et al, 2010).…”
Section: The Privacymentioning
confidence: 99%